Application Of Jean Watson's Model Theory With The Application Of Progressive Muscle Relaxation In Hypertensive Patients At The Tapus Health Center, Lebong Regency In 2022 - Yanti, Nini Fitri; Desmetasari, Desmetasari; Sofais, Danur Azissah roeslina (Universitas Dehasen Bengkulu, 2023)
Intoduction: Hypertension is a systemic blood pressure in which systolic pressure>140 mmHg and dystolic >90 mmHg. High blood pressure or hypertension is a medical condition in which there is a chronic increase in blood pressure (over a long period of time). People who have at least three blood pressure readings that exceed 140/90 mmHg at rest are thought to have high blood conditions. Always high blood pressure is one of the risk factors for stroke, heart attack, heart failure and arterial aneurysm, and is a major cause of chronic heart failure.This study uses a method that is a nursing process approach based on the chosen nursing theory, the techniques used in data collection are interviews, observations, physical examinations and conducting nursing care. The source of data obtained or used is primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is to study source books related to nursing care given to patientsThe result of nursing care in hypertensive patients using progressive muscle relaxation techniques is to focus on a muscle activity, by identifying tense muscles then lowering tension by doing relaxation techniques to get a feeling of relaxation. Progressive muscle relaxation techniques are done by relaxing or resting the muscles, mind and mental and aim to reduce anxiety.Jean watson's theory can be applied and applied well in the treatment of focusing on cases of hypertension with progressive muscle relaxation actions. Advice for patients and families to maintain good health both physical, psychological and dietary health to prevent complications due to high blood pressure